Mechanical behavior of coating mortars through the insertion of ash from the sewage sludge (Research, Society and Development, 2022)
Through environmental policies that provide a gradual discussion about the disposal of waste produced in the most diverse industrial sectors, sewage sludge is emphasized by the problematic destination of the toxic compounds that compose it, compromising its disposal. Based on the need to implement measures to mitigate environmental impacts through the production of eco-efficient materials, the application of the ashes of sanitary sewage sludge as a partial substitute for Portland cement is currently being used as a coating mortars study. This replacement has a focus, besides reducing the large volume of sludge generated by Sewage Treatment Plants, to allow an attenuation in the consumption of cement, a large CO2 generator during its manufacturing process. It could be observed that the use of the calcined residue applied in mortar, ratifies a relevant physical-mechanical performance to the material, which compared to the material without the use of it, has better results coming from its reactivity provided by action of the thermal process of degradation.